2018
DOI: 10.1111/1462-2920.14475
|View full text |Cite
|
Sign up to set email alerts
|

Gene cluster conservation identifies melanin and perylenequinone biosynthesis pathways in multiple plant pathogenic fungi

Abstract: Summary Perylenequinones are a family of structurally related polyketide fungal toxins with nearly universal toxicity. These photosensitizing compounds absorb light energy which enables them to generate reactive oxygen species that damage host cells. This potent mechanism serves as an effective weapon for plant pathogens in disease or niche establishment. The sugar beet pathogen Cercospora beticola secretes the perylenequinone cercosporin during infection. We have shown recently that the cercosporin toxin bios… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 69 publications
(124 reference statements)
0
13
0
3
Order By: Relevance
“…Other prominent examples for PQs are the phytotoxic cercosporin or elsinochrome, which are produced by Cercospora subsp. and Elsinoë ( 47 ). The gene clusters required for those two toxins have been characterized to some extent ( 48 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other prominent examples for PQs are the phytotoxic cercosporin or elsinochrome, which are produced by Cercospora subsp. and Elsinoë ( 47 ). The gene clusters required for those two toxins have been characterized to some extent ( 48 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was some evidence that the melanin biosynthesis pathway may be involved in elsinochrome biosynthesis ( 49 , 50 ). However, later it was shown that the PQ and the DHN melanin synthesis routes are separate pathways in Colletotrichum beticola and in Elsinoe fawcettii ( 47 ). Hence, the biosynthesis of PQs is still controversial and not solved, despite the great importance of many of such substances as virulence facilitators in plant-pathogenic fungi as mycotoxins or novel anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…pers. ) Durante la exploración de los genes de patogenicidad y virulencia conocidos en Cercospora, en la presente tesis se detectaron 4 genes previamente descriptos en C. beticola, involucrados en la biosíntesis de melanina-DHN (Ebert et al, 2019). Si bien el gen central, que codifica para la melanina-DHN PKS (una policétido sintasa), se encuentra conservado entre las especies exploradas, algunos genes como CB0940_09636 (tetrahidroxinaftaleno reductasa) y CB0940_09639 (prefoldina) presentan cierta variabilidad entre especies de Cercospora que quizás podrían contribuir en diferencias de patogenicidad.…”
Section: Discussionunclassified
“…Se cree que este cluster es más amplio, incluyendo genes adicionales (Schumacher, 2016;Ebert et al, 2019) (Martins et al, 2004).…”
Section: Discussionunclassified
See 1 more Smart Citation